CSR, Environmental Performance, and Financial Outcomes: Indonesian Food Industry Insights: CSR, Kinerja Lingkungan, dan Hasil Keuangan: Wawasan Industri Makanan Indonesia - Anita Sari; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to assess the impact of corporate social responsibility (CSR) and environmental performance on financial performance in Indonesian food and beverage companies. The study uses a quantitative method and a purposive sampling technique to select a sample of 14 companies listed on the Indonesia Stock Exchange from 2019 to 2020. The results show that CSR has a negative and significant impact on financial performance, while environmental performance has a positive and significant impact on financial performance. These findings suggest that companies should prioritize environmental performance to improve their financial performance.Highlights : CSR Impact: Significant negative influence on financial performance in Indonesian food and beverage companies. Environmental Performance: Positively correlates with financial outcomes, emphasizing its importance in business strategies. Sustainable Prioritization: Companies urged to prioritize environmental performance for enhanced financial results. Keywords:CSR, Environmental Performance, Financial Performance, Indonesian Companies, Sustainable Business